ISOLATION AND IDENTIFICATION OF CHOLESTEROLOXIDASE PRODUCING Pseudomonas Aeruginosa - Jasim, Hameed; Diwan, Saddam (Iraqi Journal of Science, 2024)
Cholesterol oxidase (EC:1.1.3.6) is industrially and commercially important forthe application in bioconversions for clinical determination of total or free serumcholesterol, and in food industry, for this reason this study was aimed to isolatecholesterol oxidase producing Pseudomonas aeruginosa from different localsources, by taking 55 swap samples from different serological samples includes ears,urine, burns, wounds and sputum, in addition to another 35 environmental samplescollected from soil and water from different locations in Baghdad governorate. Fromthese samples 115 bacterial isolate were obtained, and among them only 60 isolatewere identified as P. aeruginosa according to the results of biochemical tests andApi 20E system. Ability of these isolates in cholesterol oxidase production wasscreened in Lauria-Broth medium. Results showed that all of these 60 isolates wereable to produce cholesterol oxidase with variable capacities, among themP.aeruginosa H48 was the most efficient isolate in enzyme production. The activityof crude enzyme in culture filtrate of this isolate was 1.71 U/ml. Cholesterol oxidaseproduced by P.aeruginosa H48 was purified by ammonium sulphate precipitation(70% saturation), dialysis and ion exchange chromatography using CM–cellulose.The enzyme activity of the partially purified enzyme was increased to 3.87U/ml. Optimum pH and temperature for activity and stability of the partially purifiedenzyme were estimated. Results showed that the Optimum pH for enzyme activityand stability was pH7.0 and pH 6.5 respectively, while the optimum temperature forenzyme activity and stability was 35 and 37°C respectively.